Temperature sensitive emission color tuning and white light emission in segmented OPV polymer: perylene bisimide supramolecular complex - Shinde, Shekhar; Asha, S. K. (Macromolecules, 2016)
An oligo(phenylenevinylene) (OPV) based segmented polymer (POPV) and its small molecule model compound (SOPV) were designed with a carboxyl functionality in the side chain. The polymer and small molecule were complexed with pyridine functiorialized perylene bisimide (UPBIPy) and the properties of the donor: acceptor (D:A) complexes were compared. Both polymer and small molecule D:A complexes formed lamellar morphologies in the <10 nm length scale, which could be visualized by TEM and AFM imaging. The flexibility of the segmented polymer architecture imparted special properties to the polymer and its complex. The polymer complex (POPVC) exhibited white light emission with CIE color coordinates (0.27, 0.32) due to partial energy transfer from POPV to UPBIPy. The analogous model OPV complex (SOPVC) continued to show characteristic blue OPV emission in the complex also. The higher sensitivity of polymers toward temperature was made use of to tune the emission color in the complex from white (0.27, 0.32) at 30 degrees C to yellow-green (0.29, 0.31) at 100 degrees C and back to white (0.27, 0.31) upon cooling to 30 degrees C. Such a temperature sensitive emission color tuning was not observed in the small molecule complex under identical conditions.